Sense and communicative syncretism of the french advertising discourse in the field of "Produits de luxe" - Voitenko , Mariya (Current issues of Ukrainian linguistics: theory and practice, 2018)
Research in the field of advertising discourse is relevant, since advertising plays an important role in the modern society. The meaning content of the advertisement depends on the communicative parameters of the messages, which in their turn are determined by a whole number of extralinguistic factors and contextual conditions. In general, sense is a wide notion, whose search is a permanent problem of humanity. Many scientists have long been trying to give a definition of the sense that would perfectly represent its nature. The article deals with the study of the process of sense generation during communicative interaction between the addresser and the addressee in the French advertising discourse of "luxury goods". While considering the mechanisms of sense generation, the communicative activity of the person is the focus of attention and it "launches" the sense mechanisms of actualization and contextualization. The author uses the three-level classification of operators to analyze the French advertising discourse of "luxury goods" and discribes what kind of communicative actions will happen on each level. The space of discursive senses is elaborated by the valorisation of certain configurations of categorical features, expressed by discursive instances and their relations. The author examines the discursive instances of the I and the Other and illustrates the relations they mostly maintain with different examples of the recent French advertisement in the field of "luxury goods". The article reveals how the communicative syncretism of the French advertising discourse in the field of "luxury goods" manifests itself and what kind of senses this discourse valorizes. Also the attention is paid to the notion of hyperreality and the place which it takes in the French advertising discourse of "luxury goods". Hyperreality is a new linguistic state of society, in which simulation in advertising as a sign system becomes a generator of reality, and through advertisement the society of mass culture and consumption continuously ratifies itself. There is also established the main function of interaction between the discursive instances and detected how the fixation of senses discloses in the French advertising discourse of "luxury goods” on the level of their generalization.